2021
DOI: 10.17645/pag.v9i1.3607
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Interactions between SDGs and Urban Sustainability Transformations in Covid-19 Times

Abstract: Given the potential of cities to contribute to a more sustainable world as framed by the Sustainable Development Goals (SDGs) of the UN 2030 Development Agenda, this article focuses on Urban Sustainability Transformations. We take a closer look at the potentials, contradictions and challenges that SDG implementation in cities involves in light of the current Covid-19 pandemic. We argue that SDG implementation needs to consider these global challenges in order to pursue its transformative approach. As a startin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 57 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…These findings are consistent with the studies by [6,54]. They also match [55][56][57], who suggest that the unprecedented health crisis due to the COVID-19 pandemic and its economic effects necessitate a reevaluation of banks' priorities concerning the SDGs in response to urgent health needs (SDG 3) and economic disruptions (SDGs 8 and 9). Ref.…”
Section: Evolution Of Sdg Prevalence Over Timesupporting
confidence: 89%
“…These findings are consistent with the studies by [6,54]. They also match [55][56][57], who suggest that the unprecedented health crisis due to the COVID-19 pandemic and its economic effects necessitate a reevaluation of banks' priorities concerning the SDGs in response to urgent health needs (SDG 3) and economic disruptions (SDGs 8 and 9). Ref.…”
Section: Evolution Of Sdg Prevalence Over Timesupporting
confidence: 89%
“…Indeed, SDG 3 is the goal for which major discrepancies in previous studies could be reported. However, due to time constraints, our findings do not fully take into consideration research investigating the effects of COVID-19, which is rising [128] and has affected mostly SDGs 1, 2, 3, 4, 5, 8, 10, and 16 [179]. Research should pursue addressing explicitly SDG 3, its interlinkages with other goals, and the effects of the pandemic in slowing down the pathway towards the achievement of the SDGs [36] to finally foster new solutions.…”
Section: Literature Gapsmentioning
confidence: 82%
“…Since the bibliographic review carried out by Sharifi and Khavarian-Garmsir (2020) on the impact of COVID in cities, accumulating studies have indicated that analyses should involve the granular disaggregation of data to the neighborhood level ( Fu and Zhai 2021 ; Kayanan, Moore-Cherry, and Clavin 2021 ; Krellenberg and Koch 2021 ; Liu et al 2021 ; Viezzer and Biondi 2021 ). Interesting analyses have looked at cities from both developed and developing countries, especially large metropolises such as New York, Chicago, Ontario, London, Rio de Janeiro, Barcelona, Madrid, etc.…”
Section: Theoretical Frameworkmentioning
confidence: 99%